Digital Literacy and Information-Seeking Behavior by Length of Study in the Generative AI Era - Ardi, Berliani; Rahmi, Rahmi; Gani, Fuad (Universitas Jambi, Magister Program of English Education Department, 2026)
In the era of generative artificial intelligence (AI), university students must not only access digital information but also evaluate, verify, manage, and use it ethically for academic purposes. This study examines the relationship between academic digital literacy and academic information-seeking behavior among students at AZ University and explores whether this relationship differs by length of study, represented by admission cohort. Using a quantitative cross-sectional design, data were collected from 246 respondents through a four-point Likert-scale questionnaire. The analysis included reliability testing, descriptive statistics, correlation, regression, cohort comparison, and moderation analysis. The results showed good reliability, with Cronbach’s alpha values of 0.817 and 0.806. Academic digital literacy was strongly and positively associated with academic information-seeking behavior, r = 0.639, p < 0.001, explaining 40.8% of its variance. A planned undergraduate comparison showed a stronger association among first-year students, highlighting the importance of early academic digital literacy support.